The Pure green: mobile-based recycling waste pickup service: PURE GREEN: MOBILE BASED RECYCLING WASTE PICKUP SERVICE - Ita Setiani; Qurrotu Aiini Najaah; Intan Ramadhany; Shelsabella Qoulan Sadida; Lutfhi Hamid Muhram (CATHA SAINTIFICA, 2024)
The increasing amount of indiscriminate waste disposal and the use of non-recyclable waste. Waste problems in Indonesia include the increasing amount of waste generated by the community, the lack of places for waste disposal. Waste management is still a very important issue. With so much waste, there can be many problems. This allows the accumulation of waste caused by delays in the waste pickup process. Therefore, a new design is needed to be a solution to the problem. This research is to design the UI/UX of a recyclable waste pick-up service application called Pure Green based on Mobile using the Unified Modeling Language (UML) as the basis for modeling. This research was conducted at TPS 3R which is located in Talunombo Village, Sapuran District, Wonosobo Regency. The methods we used in this research were observation, interviews and literature study. We also used the system development model. With this application design, it is expected that garbage pickup can be done more effectively and efficiently, so that the problem of garbage accumulation can be minimized and environmental cleanliness will be maintained. This research is the first step in developing technological solutions for better waste management.